Maternal Obesity and initiation and duration of Breastfeeding: Data from the Longitudinal Study of Australian Children - Amir, L.H.; Donath, S (My University, 2008)
As breastfeeding is important for child health, it is essential to investigate the possible relationship between maternal obesity and poorer infant feeding outcomes. Lower breastfeeding initiation in overweight/obese women has been found in the US, UK and Australia. Shorter duration of breastfeeding in overweight/obese women has been found in the US, Australia and Denmark. This paper uses a cross sectional survey to look at whether the lower rate of breastfeeding at six months by overweight and obese mothers is primarily due to these women giving up breastfeeding in the first week postpartum. The sample used is children from the infant cohort (about 12 months of age) of Wave 1 (2004) of the Longitudinal Study of Australian Children for whom breastfeeding and maternal information were available.
Keywords: Families -- Mothers; Health -- Breastfeeding; Health -- Obesity; Families; Health; Health and wellbeing; Families and relationships; Health; Families; Mothers; Breastfeeding; Obesity; Health and wellbeing; Families and relationships